LEADERSHIP DEVELOPMENT TO FACE GLOBAL ECONOMIC CHALLENGES - Loso Judijanto; Arifatul Hasanah; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Facing the challenges of an increasingly complex global economy, human resource (HR) leadership development is crucial to organisational success. Competent and adaptive leaders are needed to guide organisations through market changes, technological disruption and geopolitical uncertainty. Therefore, organisations need to implement a comprehensive and visionary leadership development strategy that includes identifying potential leadership talent, providing relevant learning and development opportunities, and creating a culture that supports leadership growth and innovation. Investment in HR leadership development is not only a strategic imperative, but also a competitive advantage that can drive team performance, increase employee engagement, and align the organisation towards common goals. However, leadership development must be an ongoing and evolving endeavour, responsive to changing business realities and emerging needs. By adopting a proactive and future-oriented approach to HR leadership development, organisations can position themselves for success in an increasingly competitive global landscape.